Viral immunology and immunopathology - Notkins, Abner Louis (Academic Press, 1975)
Viral Immunology and Immunopathalogy covers topics concerning the role of cellular and humoral immunity in viral infections, factors responsible for the persistence and recurrence of viral infections in the presence of immunity, mechanisms of viral immunopathology, and concepts in the development of vaccines. The book describes the history of viral immunology; the synthesis and properties of viral antigens; and the humoral immune response to viruses. The text also discusses the mechanisms of viral neutralization; cellular immunity; the role of inflammatory cells and effector molecules in combating viral infections; and the genetic control of resistance. The book concludes with chapters on herd immunity; viral immunopathology; and viral immunology and immunopathology. Immunologists, pathologists, virologists, and microbiologists will find the book useful.